Residual Amount of HBV DNA in Serum is Related to Relapse in Chronic Hepatitis B Patients After Cessation of Nucleos(t)ide Analogs. Issue 4 (April 2015) - Jiang, Jian-ning; Huang, Zhan-lian; He, Li-xia; Huang, Yue-hua; Su, Ming-hua; Xie, Rong; Liang, Yan-xiu; Fu, Wu-dao; Huang, Xiao-hong; Guo, Wen-wen; Zhong, Shao-hua; Liu, Zhi-hong; et al.
Abstract : Objective: To investigate the relationship between relapse and the levels of the residual amount of HBV DNA in serum at cessation in chronic hepatitis B patients meeting 2008 Asian Pacific Association for the Study of the Liver (APASL) nucleos(t)ide analogs (NAs) cessation criteria. Methods: A total of 72 chronic hepatitis B patients who took NAs and had reached 2008 APASL cessation criteria entered the study. Patients were followed up for 6 months or longer after antiviral therapy was stopped. Serum HBV DNA level at cessation was detected by a highly sensitive polymerase chain reaction assay with detection limitation of 2 IU/mL. Results: Of all the 72 patients, 42 patients (65.3%) relapsed after NA cessation. The detectable rate of the trace amount of HBV DNA at cessation was 41.7% by highly sensitive polymerase chain reaction reagents. The detectable rate of patients with consolidation treatment duration of <18 months was higher than that with consolidation duration of ≥18 months (47.5% vs. 15.4%, P =0.034), and the detectable rate of patients with HBeAg seroconversion within 6 months of treatment was lower than that of ≥6 months (25.0% vs. 61.5%, P =0.036). The residual amount of HBV DNA and detectable rate at cessation showed significant differences between relapsed and nonrelapsed patients (130.4±420.90 vs 44.6±155.16 IU/mL, P =0.004; 55.3% vs. 16.0%, P =0.001). The cutoff value predicting relapse was 2.24 IU/mL, with a sensitivity of 0.553 and specificity of 0.840. Conclusions: Residual amount of HBV DNA in serum at NA cessation is associated with HBV relapse. The cutoff value predicting relapse was 2.24 IU/mL, with a sensitivity of 0.553 and specificity of 0.840.